Sex hormones, sexual activity and plasma anticonvulsant levels in male epileptics. Issue 9 (September 1983) - Toone, B K; Wheeler, M; Nanjee, M; Fenwick, P; Grant, R
Abstract : Testosterone, LH, FSH, PRL, and sex hormone binding globulin (SHBG) were measured in 72 male epileptic patients on chronic anticonvulsant drug regimes. Sexual activity was estimated and plasma anticonvulsants measured. Total testosterone (TT), LH, FSH, PRL, and SHBG were increased; free testosterone (FT) was decreased. Sexual activity appeared diminished particularly in relation to reduced FT.